AMIODARONE-INDUCED THYROID DYSFUNCTION: CLINICAL CASE WITH LITERATURE REVIEW - Bogun, L. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article addresses the problem of amiodarone-induced thyroid dysfunction based in the clinical case. The literature data on the pathogenesis, diagnosis of this disease, as well as management tactics for different variants of amiodarone-associated thyroid dysfunction are shown.Transient changes in thyroid function tests often occur in euthyroid individuals treated with amiodarone. Amiodarone causes predictable changes of tests that characterize the function of the thyroid gland, explicable in terms of physiological effects, caused by an iodine excess and its inhibition of deiodinase activity. Identify euthyroid hypothyroxinemia should not be considered as an indication for the abolition of amiodarone. While patients with pre-existing autoimmune thyroid disease (subclinical Hashimoto's thyroiditis or positive antithyroid antibodies) are at increased risk of developing amiodarone-induced hypothyroid-dism, most patients remain euthyroid during amiodarone therapy. Since small increases in serum TSH concentrations (10 to 20 mU/L) are seen in euthyroid patients for the first three to six months after amiodarone therapy is initiated, amiodarone-induced hypothyroidism should only be diagnosed when serum T4 concentrations are low-normal or low, or mild TSH elevation persists.